Humanistic Criminology: Roots from Peter Kropotkin - Stevenson, Lois E. (1985)
Kropotkin's extensive writings on criminological issues have been almost totally neglected. Through critical historical and macro-structural analyses Kropotkin assessed institutional arrangements disclosing how they were or were not meeting human needs. Our exploration focuses on Kropotkin's theoretical contributions, his feelings-based criminology and his extremely insightful dualistic conceptualization of human nature . His contributions to penology, and his assessment of social arrangements which would meet the complex and ever-changing needs of humankind are briefly examined. Kropotkin's analytic framework provides an insightful and provocative base from which to synthesize criminological thought and research and from which to take action to alter social arrangements which do not meet human needs